2010
DOI: 10.1308/003588410x12664192076133
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy: a personal series of 140 consecutive cases

Abstract: Ann R Coll Surg Engl 2010; 92: 398-402 398Since the first laparoscopic splenectomy in 1991, 1 the procedure has been rapidly established as a safe and effective treatment for a range of benign and malignant haematological conditions. The procedure has tended to take longer than open splenectomy with median operating times in recently reported series of 85-231 min; 2-6 however, it is associated with low morbidity rates of 18-26% 2,5,7 and zero mortality in some series 5,7-10 with others recently reporting morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
1
16
0
2
Order By: Relevance
“…One patient each experienced wound hematoma, gastrointestinal bleeding, and cerebral infarction. Pattenden et al 20 reported an overall complication rate of 15% ( 20 In this study, the mean spleen weight was 294.9 g (range, 31∼2,564 g). The maximum spleen size was 30 cm in length and 22 cm in width.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…One patient each experienced wound hematoma, gastrointestinal bleeding, and cerebral infarction. Pattenden et al 20 reported an overall complication rate of 15% ( 20 In this study, the mean spleen weight was 294.9 g (range, 31∼2,564 g). The maximum spleen size was 30 cm in length and 22 cm in width.…”
mentioning
confidence: 59%
“…[19][20][21] This study had longer operation time than earlier studies owing to the delicate and careful handling during LS to minimize surgical complications and avoid open conversion in difficult cases that were indicated for LS. Further, this study had a relatively small group of 52 patients, which is lower than those of other studies.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Laparoscopic splenectomy (LS) in the pediatric age group is generally accepted as a technically demanding procedure, which needs experience. [7][8][9][10][11] Although widely used, the studies analyzing the outcomes for LS surgeries are very inconclusive in the literature. 12 The purpose of this study is to present the long-term followup results of a case series of children who underwent LS for a variety of hematologic disorders, evaluate possible complications and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] La esplenectomía laparoscópica (EL) en la población pediátrica está en general aceptada como un procedimiento técnicamente complejo que requiere de experiencia. [7][8][9][10][11] Si bien es un procedimiento ampliamente utilizado, los estudios que analizan los resultados de las EL hallados en la bibliografía no son concluyentes. 12 El objetivo de este estudio es presentar los resultados del seguimiento a largo plazo de una serie de casos de niños sometidos a una EL por diversos trastornos hemáticos, evaluar las complicaciones posibles y los resultados.…”
Section: Introductionunclassified